Human Development in South Asia 1999 : The Crisis of Governance - Mahbub ul Haq Human Development Centre; Desktop composition by Jawaid Iqbal; Cover design by Khalid Bin Majeed (Karachi Oxford University Press, 1999)
This volume analyzes governance issues from the perspective of political, economic, social and civic dimensions, provides an in-depth analysis of the phenomenon of corruption, and advocates a concrete and realistic reform agenda necessary for promoting "human governance" in the region.
Include Illustrations, Tables and Key to Indicators.
This publication covers nearly all Crisis of Governance
Keywords: South Asia -- Economic history -- Economic policy -- Social policy -- Politics and government -- Social conditions